2022
DOI: 10.3390/biomedicines10102404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fecal Microbiota Transplantation for Clearance of Multidrug-Resistant Organisms under Multiple Comorbidities: A Prospective Comparative Trial

Abstract: Fecal microbiota transplantation (FMT) could decolonize multidrug-resistant organisms. We investigated FMT effectiveness and safety in the eradication of carbapenem-resistant Enterobacteriaceae (CRE) and vancomycin-resistant enterococci (VRE) intestinal colonization. A prospective non-randomized comparative study was performed with 48 patients. FMT material (60 g) was obtained from a healthy donor, frozen, and administered via endoscopy. The primary endpoint was 1-month decolonization, and secondary endpoints … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…This is the process of taking donated stool from screened healthy donors and processing it into a treatment administered to recipients for the purpose of improving their health. FMT is now well-established, and guidelines recommend treatment with FMT for patients suffering from recurrent Clostridioides difficile infection (rCDI), in whom the gut microbiota has become extensively disrupted or ‘dysbiotic’ [ 50 , 51 ]. FMT is postulated to work by reversing these perturbations and re-establishing a ‘healthy’ microbiota and metabolome that resists the outgrowth of C. difficile [ 52 ].…”
Section: Strategies To Reduce Expansion Of the Gut Resistome By Modul...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is the process of taking donated stool from screened healthy donors and processing it into a treatment administered to recipients for the purpose of improving their health. FMT is now well-established, and guidelines recommend treatment with FMT for patients suffering from recurrent Clostridioides difficile infection (rCDI), in whom the gut microbiota has become extensively disrupted or ‘dysbiotic’ [ 50 , 51 ]. FMT is postulated to work by reversing these perturbations and re-establishing a ‘healthy’ microbiota and metabolome that resists the outgrowth of C. difficile [ 52 ].…”
Section: Strategies To Reduce Expansion Of the Gut Resistome By Modul...mentioning
confidence: 99%
“…Shin and colleagues undertook a non-randomised controlled trial in multimorbid adult participants colonised with CRE or VRE over a two-year period in Korea [ 51 ]. Treatment allocation to FMT was assigned by participant preference.…”
Section: Strategies To Reduce Expansion Of the Gut Resistome By Modul...mentioning
confidence: 99%
“…Furthermore, patients with CRE showed low α-diversity, reduced anaerobic bacteria producing short-chain free acids, and increased Enterobacteriaceae [19]. Our previous study showed that patients with CRE exhibited dysbiosis associated with a higher relative abundance of Enterobacteriaceae [5]. Significantly, the reduction in dysbiosis through FMT can decrease the levels of CRE [6], and the effectiveness of FMT in clearing MDRO is influenced by the extent of dysbiosis [4,5].…”
Section: Discussionmentioning
confidence: 96%
“…Our previous study showed that patients with CRE exhibited dysbiosis associated with a higher relative abundance of Enterobacteriaceae [5]. Significantly, the reduction in dysbiosis through FMT can decrease the levels of CRE [6], and the effectiveness of FMT in clearing MDRO is influenced by the extent of dysbiosis [4,5]. Probiotics may serve as a therapeutic alternative for MDRO colonization by addressing dysbiosis, even in ICU patients [7,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation